Козацький фактор у діяльності губернського та повітового чиновництва Південної України другої половини XVIII століття. (Zaporizhzhia Historical Review, 2021)
The author brings up the question of Southern Ukrainian officials’ attitude towards the cossacks. He proves that in the first years after the liquidation of Zaporizka Sich the Cossackhood found itself under strick control of local provincial and districl officials. From the other side, the process of involving former Zaporizhzhyan starshyna to administrative activities by equalizing it in ranks with Russian military officials had started.